FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT DEPRESI PADA PASIEN KANKER YANG DIRAWAT DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Rizki ' Suwistianisa; Nurul ' Huda; Juniar ' Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Depression is long sadness and anxiety that enclosed by worthless feeling and dominated by uncomfortable feeling and long strong intensity. The purpose of the research was to determine the factors that influenced the level of depression in cancer patient that being treated at RSUD Arifin Achmad Riau Province with descriptive correlation research design and cross sectional study. Sample of this research was 60 respondents based on inclusion criteria by using purposive sampling technique. Measuring tools of this research are questionnaire for family support, the level of knowledge and level of depression. The univariate analysis used to showed the frequency distribution and bivariate analysis using Chi Square test for family support variable and alternative Kolmogorov-Smirnov test for age, gender, and level of knowledge. The results of univariate analysis showed that most cancer patients was 41-60 years (60.0%), female (81.7%), has been married (100%), the last of educational was senior high school (38.3%), most medical diagnosis was breast cancer (80.0%), family support system was high (55.0%), level of knowledge was low (73.3%), level of depression was moderate (38.3%). The results of bivariate analysis showed that there is a correlation between family support system (p value 0.002) with the level of depression and there are no relationship between age (p value 0.949), gender (p value 0.917), the level of knowledge (p value 0.645) with the rate of depression. Recommended for health workers, family and social environment can reduce the rate of depression by providing information support, appreciation, emotional and instrumental. Keywords: Cancer, family support system, level of depression, level of knowledge